Abortion in adolescents, experience at Cayetano Heredia National Hospital. - Acho Mego, Segundo (2015)
OBJETIVE: To determine the incidence, demographic characteristics and complications of abortion in adolescents. MATERIALS AND METHODS: A descriptive, retrospective case series, held at the Cayetano Heredia National Hospital between 2000 and 2003. RESULTS Study type: From a total of 2222 abortions, 325 were adolescents. The incidence in adolescents was 14.7%. Most are concentrated in the age group of 17-19 years (73.6%). 59.4% interrupted their pregnancy before 17 weeks. The most common discharge diagnosis was incomplete abortion (67.1%); 12.8% agreed to have undergone abortion maneuvers and 9.4% had had a previous pregnancy. The most frequent complications were income 54.1% anemia and urinary tract infection 9.4%. CONCLUSION: The abortion occurred more frequently in late adolescence; the most common diagnosis was incomplete abortion and the most common complication of acute anemia.